Exploring the suitability of Saccharomyces cerevisiae strains for winemaking under aerobic conditions. (February 2022) - Tronchoni, Jordi; Gonzalez, Ramon; Guindal, Andrea M.; Calleja, Elena; Morales, Pilar
Abstract: Aerobic fermentation was previously proposed to reduce the ethanol content of wine. The main constraint found for Saccharomyces cerevisiae to be used under these conditions was the high levels of acetic acid produced by all S. cerevisiae strains previously tested. This work addressed the identification of S. cerevisiae wine yeast strains suitable for aerobic fermentation and the optimization of fermentation conditions to obtain a reduced ethanol yield with acceptable volatile acidity. This approach unveiled a great diversity in acetic acid yield for different S. cerevisiae strains under aerobic conditions, with some strains showing very low volatile acidity. Three strains were selected for further characterization in bioreactors, with natural grape must, under aerobic and anaerobic conditions. Ethanol yields were lower under aerobic than under anaerobic conditions for all strains, and acetic acid levels were low for two of them. Strain-dependent changes in volatile compounds were also observed between aerobic and anaerobic conditions. Finally, the process was optimized at laboratory scale for one strain. This is the first report of S. cerevisiae wine strains showing low acetic acid production under aerobic conditions and paves the way for simplified aerobic fermentation protocols aimed to reducing the alcohol content of wines. Graphical abstract: Image 1 Highlights: Great diversity in acetate yield for S. cerevisiae strains under aerobic conditions. Strains with low acetate yield can be useful for winemaking under aerobic conditions. Changes in volatile compound profile between aerobic and anaerobic conditions. Profile of volatile compounds under aerobic conditions differs between strains. A gradual decrease of oxygen availability helps to keep acetic acid levels low.